ANALISA PERSEPSI MAHASISWA TERHADAP PELAKSANAAN AUDIT PADA OPINI WTP DALAM KAITANNYA DENGAN TANGGUNG JAWAB DAN INDEPENDENSI AUDITOR - Pakambi, Siska Cantika; Elim, Inggriani; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
Expectation gap in auditing is the term used to signify the difference in expectation of wha auditor belived about auditor’s responsibility and what financial statement users belived about auditor’s actual responsibility. This study was aimed at finding out the difference of perception between the students of accounting and students of management on audit implementation on unqualified opinion in relation to responsibility and independence of auditor. This was a study using quantitative method. The population consisted of the eighth semester students of accounting and students of management Departement of S1 Program. The method of sampling used was purposive sampling method. The number of questionnaires distributed was 60 and all of them could be used in this study. The method of analysis for hypothesis testing was Independent Sample T-Test. The tool of data analysis used was SPSS version 23.0 program. Based on the result of Independent Sample T-Test analysis it was found that (1) There is a difference of perception among the students of accounting and students of management on auditor’s responsibility.(2) There is a difference of perception among the students of accounting and students of management on auditor’s independence.Keywords: Implementation on Unqualified Opinion, Expectation Gap, Students, Auditor’s Responsibility and Auditor’s independence.